2018
DOI: 10.1111/ijfs.13963
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties and fractal analysis of texturized soybean protein/wheat gluten composite produced by high moisture extrusion

Abstract: Summary Texturized soybean protein (TSP) and wheat gluten were prepared at high moisture using a twin‐screw extruder. Effects of feed moisture content, extrusion temperature and wheat gluten content on the dynamic mechanical properties, microstructures and fractal analysis of texturized soybean protein/wheat gluten composite were investigated. All extruded samples were well fitted with Burger's model in creep‐recovery tests (R2 ≥ 0.978). The creep‐recovery rate decreased with an increasing extrusion temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…Currently, the use of a twin extruder at high moisture conditions of above 40% is the most widely used and efficient process for production of meat analogues using starches and proteins as raw materials (Lin, Huff, & Hsieh, 2000, 2002; Osen, 2016; Riaz, 2000; Wu et al., 2019). By combination of thermomechanical shear treatment, the protein–water mixture is plasticized converted into a viscoelastic fluid which is then extruded through a cooling die.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of a twin extruder at high moisture conditions of above 40% is the most widely used and efficient process for production of meat analogues using starches and proteins as raw materials (Lin, Huff, & Hsieh, 2000, 2002; Osen, 2016; Riaz, 2000; Wu et al., 2019). By combination of thermomechanical shear treatment, the protein–water mixture is plasticized converted into a viscoelastic fluid which is then extruded through a cooling die.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface graph (Figure a) showed that ER increased with the increase in the moisture content from 18% to 22%. If the moisture content is high and the starch viscosity is low, it will be advantageous for uniform heating and mixing of materials, which will eventually lead to the increase of starch gelatinization (Lawton & Handerson, ), and form porous and complex fiber structure (Wu et al, ). It was obvious from Figure b that ER increased as temperature decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Rheological property experiments were operated in a controlled-stress HAAKE MARS-III rheometer (Thermo Scientific Corp, Waltham, Germany), according to the method of Wu et al [20]. The frozen dough was thawed at room temperature in a 20 mm diameter steel plate, gapped by 1 mm.…”
Section: Methodsmentioning
confidence: 99%